The Rhetoric of Political Commentary: Genre Transformations - Gabrėnaitė, Eglė (Respectus Philologicus, 2016)
Political commentary is called the genre of evaluative journalism with fundamental indication, the expression of subjective opinion, on purpose to explain political phenomena and to assess it. From the perspective of rhetoric science positions, the most important is the argumentative level of commentary, i.e., persuasive substantiation of author’s propositions with its various forms: from argued reasoning and discussion what brings commentary closer to analytical genre to the usage of manipulative eristic argumentation. This article analyses the comments of political reviewers which are different from published comments in printed and electronic media: structurally they are too fragmented to identify them as traditional comments; they are different from new genre of internet comments as usually they are the product of multidirectional interactive reflection with the content and expression forms that are predetermined by specific communication circumstances. Political commentary is explored as political rhetoric expression form on purpose to identify and reveal the changes of political commentary and to define the factors that inspire them.